The effect of extracellular potassium on the intracellular potassium ion activity and transmembrane potentials of beating canine cardiac Purkinje fibers (The Rockefeller University Press, 1977)
We used open tip microelectrodes containing a K+-sensitive liquid ion exchanger to determine directly the intracellular K+ activity in beating canine cardiac Purkinje fibers. For preparations superfused with Tyrode's solution in which the K+ concentration was 4.0 mM, intracellular K+ activity (ak) was 130.0+/-2.3 mM (mean+/-SE) at 37 degrees C. The calculated K+ equilibrium potential (EK) was -100.6+/- 0.5 mV. Maximum diastolic potential (ED) and resting transmembrane potential (EM) were measured with conventional microelectrodes filled with 3 M KCl and were -90.6+/-0.3 and -84.4+/-0.4 mV, respectively. When [K+]o was decreased to 2.0 mM or increased to 6.0, 10.0, and 16.0 mM, ak remained the same. At [K+]o=2.0, ED was -97.3+/-0.4 and Em - 86.0+/-0.7 mV; at [K+]o=16.0, ED fell to -53.8+/-0.4 mV and Em to the same value. Over this range of values for [K+]o, EK changed from - 119.0+/-0.3 to -63.6+/-0.2 mV. These values for EK are consistent with those previously estimated indirectly by other techniques.